Transcriptomes analysis of an indigenous thermotolerant yeast pichia kudriavzevii UniMAP 3 - 1 under acetic acid and thermal stress during ethanol production - Khadijah Hanim Abdul Rahman (School of Bioprocess Engineering, 2018)
This research is focusing on the study of transcriptomes profiling of thermotolerant yeast following the presence of acetic acid in individual glucose and xylose media under thermal stress. Indigenous yeasts with the capability to utilize xylose at high temperature were isolated from environmental samples that have potential of lignocellulosic degrading activity at high temperature. The isolated yeasts were screened for their ethanol production on glucose and xylose at high temperature (40oC) and characterized morphologically and molecularly.